The Impact of Exchange Rate and Inflation on Economic Growth: Empirical Evidence from the MENA region using Panel Data Analysis - Mohamed, ES-SANOUN; Khaoula , ELMOUSSAOUI; Idriss , OUALI; Meryam, EL-ABBADI; Mounir , BENBOUBKER (Journal of Ecohumanism, 2025)
The volatility of exchange rates and inflation represents a critical challenge to economic stability in the MENA (Middle East and North Africa) region. This study delves into the complex relationship between these macroeconomic factors and economic growth from 2000 to 2023, with a focus on providing actionable insights for policymakers. Using a panel dataset of nine MENA countries, the research employs Feasible Generalized Least Squares (FGLS) to address issues of heteroskedasticity, serial correlation, and cross-sectional dependence, offering a robust analysis of the dynamic interactions. The findings reveal that inflation significantly hampers GDP growth, confirming that rising inflation undermines investment and creates economic uncertainty. In contrast, a more competitive Real Effective Exchange Rate (REER) fosters economic growth by improving export competitiveness, especially in non-oil sectors. Interestingly, the analysis also highlights that imports have a positive effect on GDP growth, emphasizing their role in supporting domestic production through the provision of essential goods and technologies. This study calls for targeted policy measures in the MENA region to stabilize inflation, enhance exchange rate competitiveness, and diversify exports. Such strategies are essential for sustaining economic growth and ensuring long-term economic stability.